SUCCESS RATE OF GLAUCOMA DRAINAGE DEVICE IMPLANTATION IN KARIADI GENERAL HOSPITAL SEMARANG 2020 – 2022 - Apriliana, Rina; Rachmi, Fifin L.; Maharani, Maharani (Majalah Oftalmologi Indonesia, 2023)
Introduction: Glaucoma is a leading cause of irreversible blindness, and implantation of drainage devices is an effective treatment option for patients with advanced glaucoma. The purpose of this study was to investigate the success rate of glaucoma drainage devices implantation in Kariadi Hospital. Methods: This was an observational analytic study with a retrospective design. All patients who received Virna implantation between January 2020 and December 2022 were included. Intraocular pressure (IOP) examination was performed at the baseline and at the first day, at the seventh day, at the first month, and at the third month after surgery. The success rate was divided into three groups: complete success if IOP was <21mmHg without medication, qualified success if IOP was <21mmHg with medication, and failure if IOP was >21mmHg with medication. Results: This study included 42 patients (42 eyes) with an average age of 43.3 years. There were 16 male (38%) and 26 female (62%) patients in the group. From these patients, 11 (26.2%) had primary glaucoma and 31 (73.8%) had secondary glaucoma. There was a significant decrease in IOP from preoperative measurement (37.1±10.1mmHg) compared to IOP on the first day (13.0±6.0mmHg), on the seventh day (15.4±3.8mmHg), on the first month (18.2±4.4mmHg), and on the third month (23.4±8.9mmHg) after surgery (p<0.05). At three-month follow-up, the complete success was 14.29%, the qualified success was 50%, and the failure was 35.71%. Conclusion: Glaucoma drainage device implantation was found to successfully reduce IOP in patients with advanced glaucoma. The qualified success rate was higher than complete success rate, suggesting that some patients may require medication to achieve target IOP levels.